KAJIAN ASPEK SEMANTIK ISTILAH KEAGAMAAN PADA TEKS THE CULTURAL ATLAS OF ISLAM(Studi Evaluatif Melalui Pendekatan Kritik Holistik) - Kardimin Kardimin (Al-Misbah (Jurnal Islamic Studies), 2014)
Today the efforts of translation of books of science and technology in  Indonesia  is  increasingly  necessary.  The  need  for  translation business is done in both areas was caused by several things. First as a developing country, Indonesia wants to improve its progress in the field  of  science  and  technology.  Second,  most  of  the  science  and technology books written in foreign languages. Third, the ability of our scholars to write original work in both areas was very limited.This  study  uses  a  holistic  approach  to  criticism.  In  criticism  of holistic,  objective  factors  that  were  examined  in  this  study  is  the book Indonesian translation "Cultural Atlas of Islam" published Mizan, Bandung aslinyaaslinya book "The Cultural Atlas of Islam written by Al-Faruqi.This research resulted in the conclusion that the translation still has some drawbacks. To overcome these weaknesses need to establish some  devices  that  must  be  owned  by  a  text  translator  religious cultural nuances that can be used as a guide for translators specialized texts religious nuances. In other words that the translator in the field of religion must have very specific competencies and different from other areas of the text translator.